2D ship-like section slamming pressure numerical analysis by conformal mapping - Yasa, Ahmet Mertcan (Array, 2021)
In this paper, a method to predict slamming pressures and pressure distribution at the time of water entry for 2D sections is presented. The mathematical model is based on the Schwarz-Christoffel conformal mapping method. This conformal mapping technique has been used to calculate slamming loads during water entry. The pile-up of water during motion is also considered and an alternative pile-up coefficient is assumed against Wagner’s generalized method. A simplified and accurate method is presented, which does not include non-linear terms and jet flow in the calculated pressure distribution on monotonically increasing 2D sections like wedge shapes. Comparison with real ship sections has been done to show accuracy of the results. Finally, a simple yet powerful method is obtained to aid the initial design stage of ships.